Hematological Profile of Beef Cattle After Consuming Concentrate Feed Supplemented with Depolarized Katuk Leaf (Fedtugrow®) in Local Farmers - Ronald Tarigan; Fadjar Satrija; Muladno; Afton Atabany; Yuliantoni Queen; Agik Suprayogi (Jurnal Ilmu Pertanian Indonesia, 2025)
Fedtugrow® is a complete feed containing depolarized katuk (Sauropus androgynous) leaves and is beneficial for enhancing the productivity of both dairy and beef cattle. Depolarization technology in katuk leaves involves the removal of polar compounds from the leaf to eliminate the potential side effects resulting from katuk consumption, such as bronchiolitis obliterans and inhibition of calcium absorption. This technology could eliminate side effects without compromising the efficacy of katuk leaves in increasing milk production and body weight gain. This study aimed to evaluate the efficacy of Fedtugrow® in promoting the growth of beef cattle and its impact on the health status of the cattle raised on smallholder local farms with distinct characteristics compared to commercial farms. Ten Limousin male cattle entering the fattening phase were divided into a control group that consumed standard concentrate and a treatment group that consumed Fedtugrow® for three months. Blood was collected at the end of treatment for hematological analysis, including erythrocyte and leukocyte profiles. Cows consuming Fedtugrow® showed a significantly higher average daily gain and lower stress index than the control. Furthermore, no significant differences were observed in the hematological profile, such as total erythrocyte count, hemoglobin level, hematocrit, and total leukocytes. This study showed the ability of Fedtugrow® as a growth promoter without negatively affecting the physiological status of beef cattle raised on smallholder farms. Keywords: Beef cattle, Fedtugrow®, hematology, smallholder local farm